The Improvement Of Debris Index And Knowledge Through Dental Health E-Book Program For Elementary School Students In Jakarta And Bali - Kristianto, Jusuf; Cahyati, Widya Hary; Yulita, Ita; Dwiastuti, Sagung Agung Putri (Jurnal Kesehatan Masyarakat, 2024)
Riskesdas 2018 show that the largest percentage of dental problems in Indonesia is dental caries (45.3%). The provision of dental health services in school is carried out through UKGS. Counseling method and tooth brushing demonstrations to promote dental health are routinely carried out for elementary school students. This method is used to change the behavior of maintaining dental health by brushing teeth properly and correctly. With current technological developments, the use of Android is common in learning activities. Android applications can be media that is favored by children. The educational program named "E-Book Dental and Oral Health Maintain" with an Android application is an innovative way to increase the behavior of maintaining dental and oral hygiene in children. The research objective was to determine the effect of e-book program with an Android application on the maintenance of dental health in children, as well as the role of parents. The sample consisted of 100 students of 5th grade elementary school. The increase of knowledge and the role of parents in improving dental health was significantly different between before and after the intervention, where p-value = 0.001. Research concluded that the knowledge and parents’ role is important in improving children's dental health.